The Influece Of Service Quqlity On Customer Sastisfcation and Customer Trust And Impaction Repurcase Intention and Site Revition - Putra Laksana, Ryan; Ruswanti, Endang (Publisher Cv. Inara, 2023)
This study aims to analyze the effect of e-service quality on customer satisfaction and trust and its impact on repurchase intention, WOM and site revisit. The contribution to this research is expected to provide information to e-commerce regarding the impact of e- service quality on increasing repurchase intention and site revisit. In this study, data collection using a questionnaire with a population of all people who have visited and bought products at e-commerce Tokopedia throughout Indonesia. The selection of respondents was based on purposive sampling method. The analytical method used is Structural Equation Modeling (SEM). The results of this study indicate that there is an influence between e- service quality and customer satisfaction in a positive direction, there is an influence between e-service quality and customer trust in a positive direction, there is an influence between customer satisfaction and repurchase intention in a positive direction, there is an influence between customer trust and customer trust. repurchase intention in a positive direction, there is an influence between customer satisfaction and WOM in a positive direction, there is an influence between customer trust and WOM in a positive direction, and there is an influence of customer trust and site revisit in a positive direction. The implication of this research is that e-commerce improves website quality both in terms of management and infrastructure, pays more attention to the service process to consumers, especially the problem of time accuracy and improves services such as 24-hour customer service.